Discourse and Racism in Hidden Figures - Nur Rachmatiya Rosa Zahra; Rasiah Rasiah (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2023)
This research aims to describe discourse and racism in the Hidden Figures movie using discourse and racism theory based on Dijk's approach. The results showed that the ten aspects of Dijk's theory of discourse and racism could be found in several characters such as speech, expressions, and actions that refer to the use of discourse and racism in the Hidden Figures movie. Two aspects of discourse and racism are most dominantly depicted in this movie, namely aspects of nonverbal structure and aspects of syntax. In the nonverbal structure aspect, the visible form of racism is the depiction of facial expressions such as anger, annoyance, and dislike as well as body movements refusing to interact for a long time with black people. Discourse and racism in the Hidden Figures movie also display racist behavior towards black people as a reflection of a system of prejudice, namely negative emotional reactions and stereotypes, namely judgments or assumptions based on groups and people's characteristics. This is illustrated by the experiences of Katherine, Dorothy, and Mary regarding the separation of public facilities such as toilets, libraries, and education.